ANALISA KINERJA SIMPANG DI KAWASAN KAMBANG IWAK KOTA PALEMBANG (STUDI KASUS SIMPANG TALANG SEMUT KOTA PALEMBANG) - Rianto, Islamiati; Wahab, Wahyuni; Rosyad, Farlin; Irham, Irham (Ensiklopedia of Journal, 2024)
Palembang City is the capital city of South Sumatra Province with a population of 1,718,440 people in 2024. The Kambang Iwak area is one of the recreational areas in Palembang City which is located in the city center. With a relatively large population in Palembang City, an adequate recreation area is needed so that there is no accumulation of people in an existing recreation area. The accumulation of people causes a buildup of vehicles which can disrupt traffic flow. The survey was conducted at the Talang Semut Intersection which connects 4 roads, namely Jalan A Rivai, Jalan Ki Ranggo Wirosantiko, Jalan KH Ahmad Dahlan and Jalan Jaksa Agung R Soerapto. The survey was conducted for 7 days starting at 06.00 - 18.00 WIB which was carried out in the Kambang Iwak Area, namely at the Talang Semut Intersection. It can be seen that the highest traffic volume at the intersection occurs on Sunday mornings. After the survey was conducted, the data obtained was analyzed with reference to the 2023 Indonesian Road Capacity Guidelines (PKJI). Based on the results of the analysis, the level of service at the Talang Semut Intersection was E.Keywords: PKJI 2023, Traffic Volume, and Intersection Performance